2019
DOI: 10.5853/jos.2018.02369
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Blood Pressure Levels with Outcomes in Acute Ischemic Stroke Patients Treated with Intravenous Thrombolysis: A Systematic Review and Meta-Analysis

Abstract: Background and PurposeAlthough arbitrary blood pressure (BP) thresholds exist for acute ischemic stroke (AIS) patients eligible for intravenous thrombolysis (IVT), current international recommendations lack clarity on the impact of mean pre- and post-IVT BP levels on clinical outcomes. MethodsEligible studies involving IVT-treated AIS patients were identified that reported the association of mean systolic BP (SBP) or diastolic BP levels before and after IVT with the following outcomes: 3-month favorable functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…Recently, several studies have suggested a significant correlation between BP values in the first 24 hours after EVT and long-term functional outcomes 2–5. Similar to previous studies on acute stage BP and the functional outcomes of patients with AIS receiving intravenous recombinant tissue plasminogen activator (rt-PA), higher BP levels and larger BP variability have been reported to be inversely correlated with functional outcomes in patients with AIS receiving EVT 6 7…”
Section: Introductionmentioning
confidence: 71%
“…Recently, several studies have suggested a significant correlation between BP values in the first 24 hours after EVT and long-term functional outcomes 2–5. Similar to previous studies on acute stage BP and the functional outcomes of patients with AIS receiving intravenous recombinant tissue plasminogen activator (rt-PA), higher BP levels and larger BP variability have been reported to be inversely correlated with functional outcomes in patients with AIS receiving EVT 6 7…”
Section: Introductionmentioning
confidence: 71%
“…The present study showed no significant associations were indicated between early SBPV after IVT and functional outcome, sICH in AIS. A recent study reported that lower pretreatment and post‐treatment SBP levels were associated with better 3‐month functional outcomes in AIS (Malhotra et al., 2019). The present study focused on the association between BPV after IVT and functional outcome in AIS.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in substudies of the Echoplanar Imaging Thrombolytic Evaluation Trial (EPITHET) and ECASS-II, high BP parameters were associated with an increased risk of PH in patients treated with recombinant tissue plasminogen activator 19 20. A recent meta-analysis showed that higher post-treatment SBP levels were associated with a poorer outcome in patients treated with intravenous thrombolysis 21. Another study showed that high SBP max levels following MT were independently associated with an increased likelihood of 3-month mortality and functional dependence 3.…”
Section: Discussionmentioning
confidence: 99%